2009
DOI: 10.1111/j.1476-5381.2009.00349.x
|View full text |Cite
|
Sign up to set email alerts
|

Niacin: a re‐emerging pharmaceutical for the treatment of dyslipidaemia

Abstract: Dyslipidaemias, particularly those characterized by the 'atherogenic profile' of high low-density lipoprotein-cholesterol and triglycerides and low high-density lipoprotein-cholesterol, are the major modifiable risk factor for atherosclerosis. The search for drugs to favourably alter such lipid profiles, reducing the associated morbidity and mortality, remains a major research focus. Niacin (nicotinic acid) is the most effective agent available for increasing high-density lipoprotein-cholesterol, but its use i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
51
0

Year Published

2010
2010
2013
2013

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(53 citation statements)
references
References 137 publications
(257 reference statements)
0
51
0
Order By: Relevance
“…Niacin may improve endothelial function through direct effects on the vasculature [149]. Compared with placebo, 12 weeks of no-flush niacin (1.5g/day) significantly improved brachial artery FMD in healthy men with low high-density lipoprotein (HDL)-cholesterol (<1.04mmol/l) [150].…”
Section: Lipid-regulating Therapymentioning
confidence: 99%
“…Niacin may improve endothelial function through direct effects on the vasculature [149]. Compared with placebo, 12 weeks of no-flush niacin (1.5g/day) significantly improved brachial artery FMD in healthy men with low high-density lipoprotein (HDL)-cholesterol (<1.04mmol/l) [150].…”
Section: Lipid-regulating Therapymentioning
confidence: 99%
“…Niacin has been shown to decrease plasma triglycerides and LDL-cholesterol by up to 35% and 15%, respectively, and increase HDL-cholesterol by up to 30% in a dose dependent manner [30]. Many of niacin's effects are thought to derive from its action on adipose tissue [73]. However, the cellular mechanism for niacin's lipidlowering effects were not fully elucidated until the identification of a G protein-coupled receptor GPR109A (HM74A) in 2003, which is highly expressed in adipose tissue, acts as a high-affinity receptor for nicotinic acid, and mediates antilipolytic effects [72,[74][75][76][77].…”
Section: Lipid Regulating Therapy (I) Statin Monotherapymentioning
confidence: 99%
“…Several clinical trials have demonstrated that niacin administration, either alone or combined with other lipid lowering agents, significantly reduces total mortality and coronary events, retards progression, and induces regression of coronary atherosclerosis. Following administration, niacin rapidly inhibits adipocyte lipolysis apparently through the inhibition of hepatic diacylglycerol acyltransferase 2: it leads to the inhibition of triglyceride synthesis and to the decrease of apolipoprotein B-containing lipoproteins; this is accompanied by a similarly rapid drop in plasma levels of free fatty acids [56] . The net effect is a reduced catabolism of HDL and a decreased accumulation of cholesterol esters in LDL particles.…”
Section: Niacinmentioning
confidence: 99%
“…The net effect is a reduced catabolism of HDL and a decreased accumulation of cholesterol esters in LDL particles. It has also been suggested that niacin may directly inhibit the uptake and catabolism of apolipoprotein AI-containing HDL particles, thus acting to further increase plasma levels of HDL [56] . The main problem with the use of niacin is connected to its side effects: administration of pharmacological doses of niacin is accompanied by unwanted effects, primarily a cutaneous reaction called flushing, which occurs in up to 90% of patients.…”
Section: Niacinmentioning
confidence: 99%
See 1 more Smart Citation